Resistin levels and inflammatory and endothelial dysfunction markers in obese postmenopausal women with type 2 diabetes mellitus. - Giandalia, A..; Alibrandi, A..; Giorgianni, L..; Lo Piano, F..; Consolo, F..; Longo Elia, G..; Asztalos, B..; Cucinotta, D..; Squadrito, G..; Russo, G. T. (Tufts University. Tisch Library., 2021)
Keywords: Resistin, Inflammation, Women, Type 2 diabetes, CHD.; Springer Open.